Dualistic wilderness in Kazuo Ishiguro’s a pale view of hills - Nan, Feng; Mohamad Rashidi Pakri (Penerbit Universiti Kebangsaan Malaysia, 2024)
Set in Nagasaki, struck by atomic bombing during the Second World War, Kazuo Ishiguro's A Pale View of Hills (1982/1990) has been explored through the lens of ecocriticism only by a few critics, and investigations into the wilderness have been underexplored. Overlooking the wilderness in this fiction may lead to a neglect of nature’s therapeutic influence on the characters. The primary aim of the present study is to examine the dualistic qualities of wilderness and highlight the nexus between wilderness and the psychology of the main characters. This study primarily employed the lens of wilderness to explore the representations of wilderness and its influences on the main characters. It concluded that, to the main characters in the fiction, wilderness is not only repulsive and frightening purgatory but also a sublime and picturesque haven, the latter of which is tonics, antidotes, and tranquillisers for people who approach and assimilate into the wilderness.